Chalakudy River Diversion Scheme, Kerala: does it show the future of canal irrigation in India? - Santhosh, Harikrishnan; Mohan, A.; George, S. L. (2019)
During the Green Revolution era, paddy cultivation was promoted with much vigor within Kerala. The canal systems that supplied timely irrigation played an important role in promoting food security within the state as rice self-sufficiency became a political concern. Under changing circumstances, paddy cultivation has seen a drastic downward trend in the last 30 years. One of the reasons for this trend is the irregularity in water supply through canals resulting from the flow fluctuations due to various hydroelectric projects that have come up in the upstream and inefficiencies arising out of low maintenance and performance management. At the same time, farmers in Kerala have largely shifted towards the cultivation of high valued cash crops. This paper presents a case study of the Chalakudy River Diversion Scheme which once served the irrigation requirements of paddy in the Chalakudy river basin. The paper tries to shed light on how farmers have adapted to the evolving nature of CRDS as they continually shift towards cash crops that require better water control. In this process, CRDS has ended up as an entity vastly different from the intent of its planners. The role of canal irrigation, changing from direct flow irrigation to complementing recharge or replenishment of groundwater and surface water storages, may point towards the imminent transformation of canal irrigation in the rest of India.